Desenvolvimento sustentável em universidades: uma análise de práticas de contabilidade, gestão e de environmental social and governance – ESG - Lima, Clayton dos Santos (2022)
This research aims to analyze the influence of sustainable accounting, management and Environmental Social and Governance - ESG practices in universities that make up the Green Metrics ranking. For this, the study had two methodological steps, a qualitative one, through a Systematic Literature Review (RSL), analysis of reports and sending a protocol to specialists, carried out in order to identify impact studies and also the main practices that are already developed by Higher Education Institutions (HEIs), seeking relevant information to develop an instrument for quantitative data collection, which was carried out through a survey with 106 HEIs listed in the Green Metrics ranking. The results presented in the qualitative stage, highlight Professor Rodrigo Lozano and Professor Rob Gray as authors with the greatest impact in the area, also highlight countries such as the USA and Spain and the Journal Cleaner Production and Sustainability, as journals with the greatest impact. At this stage also, through the literature, the collection in reports and the collection with specialists, it was possible to identify the variables applied in the institutions that make up the ranking, among these, the main ones found were: Green Campus, Planning, Quality of life, renewable energy , reduction of CO² emissions, environmental accounting, registration, control and dissemination of information, among others. In the quantitative stage, the information presented highlights a large number of correlations found, among these, the issues that deal with planning and the socio-environmental benefits generated by this practice, and may even develop issues capable of generating financial returns for HEIs. In addition, the findings highlight key factors for the development and adoption of ESG, as well as indicate important issues for accounting and management involvement and for the development of sustainability, stakeholder engagement and disclosure of information, such as: Planning and control, Green Campus, Drivers for the development of science, technology, projects and partnerships, Social and learning support, Research, development and Innovation (R&D&I), Renewable Sources. Likewise, the findings make it possible to identify actions and practices capable of boosting the sustainability performance of universities, as well as contributing to their adoption, inclusion of society in the institution's projects and also with the development of new studies.